On the role of environmental prosecutors in the fight against environmental offenses (Journal of actual problems of jurisprudence, 2018)
The article discusses examples of prosecutorial supervision in two regions of Kazakhstan ecology. The results of inspections of prosecutors and experts on ecology departments indicate the magnitude of pollution of water, air and soil of the country.Key words: ecology, environmental offenses, contamination of soil, air, water.